Analisis Faktor Risiko Akne Vulgaris Pada Pelajar - Ratna Wulandari; Dwi Nurwulan Pravitasari; Rubayat Indradi; Asri Nugrahandini Putri (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Acne vulgaris (AV) is a chronic skin disease in polysebaceous unit.The incidence of AV in Indonesia is 48-52%. Skin type and facial skin hygiene are triggers for AV. This disease is often complained to adolescents and become quite serious health problems. Someone with oily skin and lack of facial hygiene that can increase the AV phenomenon. Therefore, it is necessary to attend about skin types and facial hygiene to prevent the occurrence of AV in adolescents.It Is todetermine relationship between skin type and facial skin hygiene in teenager aged withtheexistence of AV inSMKMuhammadiyah2Malang.It use observational analytic study with cross sectional approach. Thesubjects were all students of SMKMuhammadiyah2Malang in academic year 2019/2020 who didn’t gettreatment AV from doctor. SamplingbyStratified Random Sampling, and found 79 respondents. Analyzed by Chi-squareand logistic regression.According to theChi-square test showed, other was a relationship between skin type (p=0.00) and facial hygiene (p=0.00) with AV. The logistic regression results showed thatskintype hadan effect (p=0.001) on AV with 54 times greater chance ofoilyskin type being exposed toAV.There’s relationship between skin type and facial skin hygiene in teenageraged withtheexistence ofAV inSMKMuhammadiyah2Malang.